THE LEGACY OF ODORICO PARAGUAÇU IN BRAZILIAN PUBLIC ADMINISTRATION: A CRITICAL ANALYSIS OF THE BUREAUCRACY AND INEFFICIENCY OF THE INSS - Maranhão, Romero de Albuquerque (Seven Editora, 2025)
This article proposes an analysis of the persistence of the dysfunctions of the Brazilian public administration, satirized in the figure of Odorico Paraguaçu in "O Bem-Amado" by Dias Gomes, through the observation of the contemporary challenges faced by the National Institute of Social Security (INSS). We argue that the demagogy, inefficiency and excessive bureaucracy, hallmarks of "Odoriquian" management, find worrying parallels in the problems that affect millions of insured individuals seeking access to their social security rights. Using a qualitative and exploratory approach, we compare the characteristics of Sucupira’s administration with those of the INSS, highlighting the social implications of a public service that, at times, distances itself from its fundamental purpose, and the discursive strategies used by Odorico to subject bodies and maintain power. DOI: https://doi.org/10.56238/sevened2025.021-063